Kenyon Cell Subtypes/Populations in the Honeybee Mushroom Bodies: Possible Function Based on Their Gene Expression Profiles, Differentiation, Possible Evolution, and Application of Genome Editing - Suenami, Shota; Oya, Satoyo; Kohno, Hiroki; Kubo, Takeo (Frontiers in Psychology, 2018)
Honey bees are eusocial insects and the workers inform their nestmates of information regarding the location of food source using symbolic communication, called ‘dance communication’, that are based on their highly advanced learning abilities. Mushroom bodies (MBs), a higher-order center in the honey bee brain, comprise some subtypes/populations of interneurons termed Kenyon cells (KCs) that are distinguished by their cell body size and location in the MBs, as well as their gene expression profiles. Although the role of MBs in learning ability has been studied extensively in the honey bee, the roles of each KC subtype and their evolution in hymenopteran insects remain mostly unknown. This mini-review describes recent progress in the analysis of gene/protein expression profiles and possible functions of KC subtypes/populations in the honey bee. Especially, the discovery of novel KC subtype/population, ‘middle-type KCs’ and ‘KC population expressing FoxP’, necessitated a redefinition of the KC subtype/population. Analysis of the effects of inhibiting gene function in a KC subtype-preferential manner revealed the function of the gene product as well as of the subtype where it is expressed. Genes expressed in a KC subtype/population-preferential manner can be used to trace the differentiation of KC subtypes during the honey bee ontogeny and the possible evolution of KC subtypes in hymenopteran insects. Current findings suggest that the three KC subtypes are unique characteristics to the aculeate hymenopteran insects. Finally, recent application of genome editing for the study of KC subtype functions in the honey bee is described. Genes expressed in a KC subtype-preferential manner can be good candidate target genes for genome editing, because they are likely related to highly advanced brain functions and some of them are dispensable for normal development and sexual maturation in honey bees.